Evolution of the soil water retention curve based on plastic volumetric strain - Kodikara J.; Jayasundara C. (E3S Web of Conferences, 2020)
The water retention behaviour of soil can be defined as the relationship between the degree of saturation (or water content) and suction at a constant temperature, which characterises the hydraulic behaviour of unsaturated soils, normally represented as the soil water retention curve (SWRC). The SWRC is commonly measured at nominal net stress by initially saturating a soil specimen and then subjecting it to drying and wetting paths, resulting in major drying and wetting curves. However, there is evidence that during these major drying and wetting paths and initial saturation, soil can undergo volumetric deformation with changes in void ratio, sometimes plastically. Therefore, for coupling the SWRC with mechanical behaviour, the dependency of SWRC on other state variables such as void ratio has been proposed. In this paper, an approach to defining SWRC for a particular plastic volumetric strain is presented within the generalised MPK model. The SWRC evolves as soil is subjected to wet/dry cycles, eventually approaching drying and wetting curves relevant to an environmentally-stabilised state. The performance of this model is demonstrated by the simulation of the loading/unloading/drying/wetting paths followed in a laboratory experiment. In addition, the evolution of the commonly-considered major drying and wetting curves is simulated, highlighting key features of the environmentally-stabilised line..